The City Between Freedom and Security : Contested Public Spaces in the 21st Century - Jensen, Vibeke; Rubing, Anders; Simpson, Deane (Birkhäuser, 2017)
This publication explores the contested territory between the state and corporate drive to 'securitise' urban space – and the principle of the city as a site for enacting open civil society, participatory democracy, and the freedom of speech and assembly. Starting from the disputed redevelopment of the Oslo Government Quarter since its attack in 2011, the book functions as a broader discursive platform mediating opposing positions at the intersection of architecture/urbanism and security/democracy. The book interposes essays, interviews, site drawings, a lexicon of terms, and photo-essays documenting fieldwork in the UK, USA, Israel, Palestine and Spain. Contributors include: S. Graham, M. Sorkin, D.Harvey, G. Agamben, Y. Yasky, L. Lambert, CPNI, R. V. Clarke, J. Coaffee, and O. Newman.